Analysis of Public Understanding of the Halal Products of Bank Syariah Indonesia, Sungai Penuh City Branch - Pratama, Adrian; Sarmigi, Elex (Jurnal Iqtisaduna, 2024)
The development of Indonesian Sharia Bank (BSI) is currently developing in Indonesia. Sharia banking provides benefits for the people of Sungai Penuh City, especially for those who are Muslim. The aim of using field research (empirical) like this is to assess the level of understanding of customers using BSI products at the Sungai Penuh City Branch using interview and observation methods. This research uses a qualitative descriptive method. The subjects used were customers of the BSI Sungai Penuh City Branch. The results of this research show that BSI customers’ understanding of the Sungai Penuh branch regarding the halal and halal nature of BSI products is not yet fully understood, customers still think that BSI products are not much different from conventional banks. However, customers already understand about BSI products which are related to the element of usury.